Managing a Marginal Victory: Presidential Campaign Strategy in 2024 - Griffiths, McCage (Sens public, 2024)
The 2024 United States presidential election cycle has been unprecedented in many aspects. From voter predictability to media presence and public opinion on pressing sociopolitical issues, this essay examines the events and campaign strategies that have made this cycle especially turbulent and different from those that came before it.